The issue of word play in advertising context - Mizrabova Jeren Ismailovna, (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This article is devoted to the lexical features and role of the word play and the problems of ways in reproducing. The main difficulties associated with the transformation of a word play. Moreover, the need to create original, memorable texts that can attract the attention of a potential costumer, the reasons for the interest of advertisers are investigated. The issue of word play is a multifaceted phenomenon that, performing a number of functions, occupies a special place in the texts of advertising. Wordplay is closely related to the content of the advertising and is used to attract the attention of a potential customer.